2019
DOI: 10.1257/app.20170572
|View full text |Cite
|
Sign up to set email alerts
|

Do 40-Year-Old Facts Still Matter? Long-Run Effects of Federal Oversight under the Voting Rights Act

Abstract: In 2013, the Supreme Court struck down parts of the Voting Rights Act that mandated federal oversight of election laws in discriminatory jurisdictions, prompting a spate of controversial new voting rules. Utilizing difference-in-differences to examine the act’s 1975 revision, I provide the first estimates of the effects of “preclearance” oversight. I find that preclearance increased long-run voter turnout by 4–8 percentage points, due to lasting gains in minority participation. Surprisingly, Democratic support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…South (Kuziemko and Washington 2018). A recent and growing literature has exploited the geographic variation in the VRA provisions to analyze the effect of enfranchisement on the distribution of state funds (Cascio and Washington 2014), on white backlash against the Democratic party (Ang 2019), on black elected officials in local governments and government spending (Bernini, Facchini, and Testa 2018) and on labor market outcomes (Aneja and Avenancio-Leon 2019). We contribute to this literature by studying the impact of the VRA on the police treatment of blacks.…”
mentioning
confidence: 99%
“…South (Kuziemko and Washington 2018). A recent and growing literature has exploited the geographic variation in the VRA provisions to analyze the effect of enfranchisement on the distribution of state funds (Cascio and Washington 2014), on white backlash against the Democratic party (Ang 2019), on black elected officials in local governments and government spending (Bernini, Facchini, and Testa 2018) and on labor market outcomes (Aneja and Avenancio-Leon 2019). We contribute to this literature by studying the impact of the VRA on the police treatment of blacks.…”
mentioning
confidence: 99%
“…The same report mentions that just three months after the VRA passed, "in many areas of the South, there is full compliance with the Act." Previous research has shown the big push in registration and turnout generated by the VRA (Fresh, 2018;Ang, 2019). Figure 1 illustrates this overall success of the VRA and shows the distribution of turnout rates in VRA counties (left panel) and in other counties (right panel) in the 1964 (in red) and 1968 (in blue) presidential elections.…”
Section: Voting Rights Actmentioning
confidence: 85%
“…The first presidential election after the reform benefited the Republican candidate (Richard Nixon) and a pro-segregation candidate (George Wallace). Previous research suggests that this fact is not anecdotal and that the VRA did not shift the median voter towards more redistributive policies (Fresh, 2018;Ang, 2019). Following the VRA, a dealignment process decoupled policy preferences from incomerelated issues towards race-related issues (Kuziemko and Washington, 2018).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, racial conservatives in statehouses intensified gerrymandering to create a structural advantage that favors white rural voters and allows preferred candidates to win a majority of seats with a minority of votes (Anderson, 2018). This artillery of voter suppression tactics accelerated after the 2013 Shelby County v. Holder Supreme Court ruling, which declared that states no longer needed federal pre-clearance for changes to election rules as required under the 1965 Voting Rights Act (Ang, 2018).…”
Section: Politics and The Racial Fixmentioning
confidence: 99%